1986
DOI: 10.1055/s-2007-1018424
|View full text |Cite
|
Sign up to set email alerts
|

Is there an Indication for Prophylactic Endoscopic Paravariceal Injection Sclerotherapy in Patients with Liver Cirrhosis and Portal Hypertension?

Abstract: From January 1, 1978, to January 1, 1980, a prospective controlled randomized trial comparing conservative treatment to prophylactic endoscopic paravariceal injection sclerotherapy of esophageal varices prior to hemorrhage was carried out. In all 71 patients liver cirrhosis was confirmed histologically. The two randomly assigned groups were comparable with respect to age, sex and degree of liver diseases and its histological type was also similar. Indications for endoscopic treatment were the existence of degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Various sclerosants were used at different doses and injected intra or paravariceally. The results of these trials are variable with two studies showing a significant reduction in both bleeding and mortality,54 55 one study showing a reduction in mortality but no difference in rebleeding,62 one study showing a significant increase in the risk of bleeding,59 and another significantly greater mortality 65. Due to the marked heterogeneity between these studies a meta-analysis is clinically inappropriate.…”
Section: 0 Natural History Of Varices In Cirrhosismentioning
confidence: 99%
“…Various sclerosants were used at different doses and injected intra or paravariceally. The results of these trials are variable with two studies showing a significant reduction in both bleeding and mortality,54 55 one study showing a reduction in mortality but no difference in rebleeding,62 one study showing a significant increase in the risk of bleeding,59 and another significantly greater mortality 65. Due to the marked heterogeneity between these studies a meta-analysis is clinically inappropriate.…”
Section: 0 Natural History Of Varices In Cirrhosismentioning
confidence: 99%
“…We carried out a clinical study on 15 patients (9 males and 6 females; average age, 45 + 12 years) with liver cirrhosis categorized as Child A and endoscopic evidence of degree II-IV esophageal varices with red spots but no history of bleeding [1,3,7,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…However, the real usefulness of prophylactic sclerotherapy must be verified by further controlled studies [4,6,7,17,18]. Reports on alterations in esophageal motility following sclerotherapy are often characterized by conflicting and ambiguous results because patients' case histories have not been selected and different scleroOffprint requests' to: E. Bovero therapy techniques and various methods of measurement of esophageal motility have been employed [2,5,[8][9][10][12][13][14].…”
Section: Abstract: Esophageal Varices -Esophageal Manometry -Prophylmentioning
confidence: 99%
“…Paquet, who published the first randomized controlled study on sclerotherapy prophylaxis, using his own criteria to define portal hypertensive patients at risk [37] still strongly advocated this technique after publication of a second series of 70 patients, all of whom were treated with injection sclerotherapy [51]. The inpatient mortality (13%) was not seen as a barrier to this form of prophylaxis, although overall mortality was at least 33%, with 7% of patients lost to follow-up.…”
Section: Injection Sclerotherapy Prophylaxismentioning
confidence: 99%
“…Even when the data from the remaining studies are analyzed specifically to identify subgroups that may benefit from sclerotherapy, the results are variable and inconsistent. Koch et al [51] found that in Child's grade A patients sclerotherapy conferred improved survival (p < 0.05); Potzi et al [55] also found that survival in Child's grade A patients was improved (p < 0.02) but it was not dependent on sclerotherapy. Similarly, another study showed that sclerotherapy was beneficial (p < 0.03) in patients with alcoholism as opposed to no alcoholism [55], but Triger et al [59] found that the improved survival in alcoholic cirrhotic patients compared to nonalcoholic cirrhotics at 2 years was not related to sclerotherapy.…”
Section: Injection Sclerotherapy Prophylaxismentioning
confidence: 99%